2007
DOI: 10.1086/512683
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of the Mannan‐Binding Lectin Gene and Susceptibility to Visceral Leishmaniasis and Clinical Complications

Abstract: Genotypes of the MBL2 gene predict the risk for developing VL and clinical complications in infections with L. chagasi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 35 publications
6
55
2
2
Order By: Relevance
“…Epistaxis was the sole exception, possibly a result of the symptom's lack of specificity; in addition to edema and jaundice, it has been identified to be a strong risk factor for death in patients with visceral leishmaniasis. 3,39 Altogether, these observations suggest that disease-induced malnutrition is the main factor contributing to parasite replication, which secondarily may lead to systemic inflammation, depending upon virulence factors and genetically driven host response [40][41][42][43] Therefore, the present data suggest that the association of higher parasitemia with malnutrition and with death may be caused by a nutrition-dependent immunosuppression, leading both to higher parasite burden and to disease severity. However, in opposition to our findings, a previous study 21 found higher bone marrow parasite burden in patients with better prognosis and higher mortality in those with a low parasite load observed by microscopy.…”
Section: Discussionmentioning
confidence: 57%
“…Epistaxis was the sole exception, possibly a result of the symptom's lack of specificity; in addition to edema and jaundice, it has been identified to be a strong risk factor for death in patients with visceral leishmaniasis. 3,39 Altogether, these observations suggest that disease-induced malnutrition is the main factor contributing to parasite replication, which secondarily may lead to systemic inflammation, depending upon virulence factors and genetically driven host response [40][41][42][43] Therefore, the present data suggest that the association of higher parasitemia with malnutrition and with death may be caused by a nutrition-dependent immunosuppression, leading both to higher parasite burden and to disease severity. However, in opposition to our findings, a previous study 21 found higher bone marrow parasite burden in patients with better prognosis and higher mortality in those with a low parasite load observed by microscopy.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, the absence of parasite actions or products that would harm the host cells or tissues is one more indication that the systemic pathogenicity of VL is dependent on the host response. Although inflammatory tests were not evaluated in this study, inflammation is an ordinary feature of VL, as indicated by increases in erythrocyte sedimentation rate and acute phase proteins [24][25][26] . Moreover, the proinflammatory cytokines interferon-γ, TNF and IL-6 and the chemokine IL-8 are elevated in VL as part of a broad and sustained innate response 27,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, although from the public health perspective the control of symptomatic cases is a priority, the non-use of markers for infection prevents the demarcation of transmission foci because more infections occur than cases of the disease [35][36][37][38] and the evolution from asymptomatic infected status to symptomatic status is mediated by genetic and nutritional factors. [39][40][41] Finally, as mentioned, this study is based on secondary data available in SINAN. Thus, although VL is a serious disease subject to mandatory reporting (and the treatment of which is only provided by government health services), the available data are based on passive case detection, and one cannot rule out the possibility of case underreporting.…”
Section: 13mentioning
confidence: 99%